Analisis Gaya Kepemimpinan Kepala Biro Perekonomian dalam Meningkatkan Kinerja Pegawai Kantor Gubernur Sumatera Utara - br Surbakti, Zein Zahara; Suryadi, Marliyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The position and role of the State Civil Apparatus has a significant impact on the progress of national development, both physical and non-physical. To improve the quality of civil servants, this development is very necessary and it is hoped that in the progress achieved, civil servants can carry out effectively, thereby encouraging and realizing national development goals. For optimal employee performance, proper leadership by using a leader is one of the factors that can encourage, guide, and motivate employees to excel in their work. The purpose of this study was to describe the leadership style used by the head of the economic bureau of the regional secretariat of North Sumatra Province in order to improve the performance of the employees of the economic bureau of the secretariat of the North Sumatra region.